2019
DOI: 10.3390/dj7030064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Irrigant Agitation Methods on Bacterial Elimination from Infected Root Canals

Abstract: Activation techniques are essential for root canal disinfection but may result in incomplete removal of bacteria. The aim of our study was to assess the antibacterial action of sonically, ultrasonically and laser-activated irrigation and 5.25% sodium hypochlorite (NaOCl) on Enterococcus faecalis in an infected tooth. Forty-four extracted mandibular premolars were mechanically prepared, sterilized, and inoculated with E. faecalis for 1 week. Bacterial counts after inoculation were evaluated in 4 randomly chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 46 publications
5
35
0
3
Order By: Relevance
“…Considering the limited reach of sonically activated irrigants in dentinal tubules, it has been argued that the concentration of NaOCl is more important than sonic irrigant activation to eliminate bacteria residing in dentinal tubules [22]. The present investigation confirms that sonic irrigant activation with EDDY, employed at the highest power setting, outperforms the antimicrobial effect of manual syringe irrigation but, in contrast to the studies of Hage et al [23] and Zeng et al [22], no viable microorganism were found even after an extended re-incubation period of seven days. In addition to different microbiological assays and variations in the irrigation protocols, the different makeup of tooth samples may account, at least to some degree, for these conflicting microbiological results.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Considering the limited reach of sonically activated irrigants in dentinal tubules, it has been argued that the concentration of NaOCl is more important than sonic irrigant activation to eliminate bacteria residing in dentinal tubules [22]. The present investigation confirms that sonic irrigant activation with EDDY, employed at the highest power setting, outperforms the antimicrobial effect of manual syringe irrigation but, in contrast to the studies of Hage et al [23] and Zeng et al [22], no viable microorganism were found even after an extended re-incubation period of seven days. In addition to different microbiological assays and variations in the irrigation protocols, the different makeup of tooth samples may account, at least to some degree, for these conflicting microbiological results.…”
Section: Discussionsupporting
confidence: 65%
“…In addition to different microbiological assays and variations in the irrigation protocols, the different makeup of tooth samples may account, at least to some degree, for these conflicting microbiological results. In the studies of Hage et al [23] and Zeng et al [22] exclusively single-rooted premolars were used whereas the sample of the present study included anterior teeth, premolars and palatal roots of maxillary molars. Premolars are frequently extracted in adolescence and early adulthood for orthodontic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In root canal therapy it is crucial to decrease bacterial population which colonize the root canal as much as possible [1]. The most conventional approach used for disinfecting the root canal is employing antimicrobial agents for irrigating.…”
Section: Introductionmentioning
confidence: 99%
“…The most conventional approach used for disinfecting the root canal is employing antimicrobial agents for irrigating. The irrigation performance can be improved by some methods such as sonically or ultrasonically activations [1]. Several agents are applicable as irrigant in root canal disinfection such as silver Nano fluid, sodium hypochlorite and chlorhexidine digluconate (CHX) [2,3].…”
Section: Introductionmentioning
confidence: 99%